Exchange Rates in the New EU Accession Countries : What Have We Learned from the Forerunners? - Smidkova, Katerina (IMF Working Papers; Working Paper, 2005)
Estimation and simulation of sustainable real exchange rates in some of the new EU accession countries point to potential difficulties in sustaining the ERM2 regime if entered too soon and with weak policies. According to the estimates, the Czech, Hungarian, and Polish currencies were overvalued in 2003. Simulations, conditional on large-model macroeconomic projections, suggest that under current policies those currencies would be unlikely to stay within the ERM2 stability corridor during 2004-10. In-sample simulations for Greece, Portugal, and Spain indicate both a much smaller misalignment of national currencies prior to ERM2, and a more stable path of real exchange rates over the medium term than can be expected for the new accession countries.